Akrasia and Self in Egonomics - Norkus, Zenonas (Problemos, 2000)
The article introduces Lithuanian reader into problematic of interdisciplinary discourse called egonomics or picoeconomics, and gives metatheoretical assessment of its achievements. Egonomics can be defined as the study of the strategic interaction of successsive motivational states within the person using the vocabulary and analytical techniques of the rational choice theory. As its most distinguished representatives are considered Jon Elster, George Ainslie, George Loewenstein, Thomas Schelling, Robert Nozick. The article consists of introduction and three sections. Introduction gives brief outline of the classical problem of acrasia in its most famous formulation proposed by Donald Davidson. The first section compares Davidsonian conceptualization of acrasia with the egonomic one. Two important differences are discussed. (1) Egonomics defines akrasia as intertemporally inconsistent choice analytically described by hyperbolic discounting function. In traditional (Davidsonian) perspective, akrasia is free intentional action against the better (conditional) judgement. (2) In the traditional view, the baseline is nonacratic behaviour. Such behaviour is background against which the “anomaly” of akrasia must be explained. Egonomics offers a kind of “Copernican” reversal of this view, drawing upon the work of Richard Herrnstein. He formulated and substantiated “matching law” conceived as universal law of behaviour. This law implies that “normal case” is hyperbolic discounting and “meliorating” or “locally maximising” behaviour. Such behaviour is background to consider the intertemporally consistent, globally maximising behaviour as “anomaly” or explanatory problem. This behaviour is conceived in egonomics as manifestation of learnable skill to use extrapsychic and intrapsychic techniques of precommitment. Most important case of these techniques are personal rules which were considered in the traditional philosophy of mind and action under the name of willpower. There are compared explanations of this phenomenon proposed by G. Ainslie, J. Eisler and R. Nozick. These explanations converge in the paradoxical conclusion that transtemporally consistent behaviour is possible, if irrational tendencies within the “self” are mutually neutralizing and counterbalancing. The second section investigates the potential of rational choice theory to renovate the vocabulary used for description and self-description of human self. This renovation is interpreted as continuation and rational reconstruction of the traditional discourse on the “multiple self”. Two main versions of this discourse are distinguished. In the first version (e.g., Buddha), “monolithic self” is fragmented into the successive selves; in the second one (e.g., S. Freud), it is considered as hierarchical structure. Both versions have their pendants in the egonomics, where Derek Parfit proposes neobuddhist theory of self, and James S. Coleman works with the concept of corporate self. He redescribes the relationship between Me and I in the vocabulary used by new institutional economics to analyse the relations between principal and agent. When the self in the neobuddhist perspective is fragmented into the temporally successive “subselves”, their relations can be described in terms of bargaining theory, collective action theory, social choice theory, game theory, and the theory of distributive justice. Such redescription reveals many illuminating parallels and intertwinings between the problem of intertemporaly consistent choice and the problem of interpersonal cooperation. The interperso- nal problem of distributive justice has its pendant in the problem of choice of rational life-plan, and the problem of overcoming akrasia is paralleled by that of preventing free riding in the collective action theory. The concluding third section contains a metatheoretical discusion which includes (1) the comparison of egonomics with the recent discourse on “death of man” or “expropriation of subject” in the continental philosophy, and (2) assessment of the explanatory value of egonomics. On the (1), article maintains that egonomics cannot be considered as belated AngloSaxon contribution to the continental project abovementioned. Rather, it is pursuing the goal to exhaust the remaining epistemic potential of the “intentional stance”. On the (2), egonomic fragmentation of the “monolithic self” is considered as the application of explanatory strategy called by Daniel C. Dennett “homuncular functionalism”. Like the “homuncular” facon de parler in the cognitive science, egonomic talk on “multiple self” cannot be ontologized or reified. Under certain conditions homuncular functionalist mode of analysis can have explanatory power and play heuristically indispensable role as way-station to the scientific explanation of behaviour, accomplished in the vocabularies of the construction stance and of the physical stance. Egonomics can be considered as kin to cognitive science. Cognitive science naturalises the problematic of traditional epistemology. Egonomics can be considered as naturalization of the analytic philosophy of action.